Analisis Pendapatan Usaha Penggemukan Sapi di Bantaran Krueng Aceh Kecamatan Krueng Barona Jaya Kabupaten Aceh Besar - M Shevin Armika; M Nasir Ismail; Teuku Fadhla (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
The success of a cattle fattening business depends on three elements: seeds, feed, and management. The purpose of this study was to determine the income of farmers and the effect of seeds (X1), green feed (X2), fine bran feed (X3), concentrate feed (X4), capital (X5) and labor (X6) on cattle fattening production in Krueng Aceh Subdistrict, Krueng Barona Jaya District, Aceh Besar Regency. The research method used was survey method. The sampling technique uses simple random sampling with a total sample of 24 cattle fattening farmers. The data analysis model used is income analysis and multiple linear regression analysis. The results showed that the average income received by cattle fattening farmers in Krueng Aceh Subdistrict, Krueng Barona Jaya District, Aceh Besar Regency was Rp. 18,307,861.15 for 2 cows per one cattle fattening period for 6 months of production. Based on the simultaneous test (F test) shows that Fcari > Ftabel means accept Ha reject Ho that seeds (X1), green feed (X2), fine bran feed (X3), concentrate feed (X4), capital (X5), labor (X6), significantly affect the production of fattening cattle (Y). While the partial test (t test) variables of seeds (X1), green feed (X2), capital (X5) and labor (X6) where tcari > ttabel then accept Ha and reject Ho means partially significant effect on cattle fattening production (Y). However, the variables of fine bran feed (X3) and concentrate feed (X4) where tcari < ttable then accept Ho and reject Ha, meaning that partially does not significantly affect the production of cattle fattening (Y). The R2 value is 0.986, this indicates that the relationship between the independent variable and the dependent variable is 98.6% while the remaining 0.4% is explained by other factors outside the model.